2003
DOI: 10.1016/s0306-4522(02)00584-5
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing characteristics of serotonin and non-serotonin-containing cells in the dorsal raphe nucleus: electrophysiological and immunohistochemical studies

Abstract: The membrane properties and receptor-mediated responses of rat dorsal raphe nucleus neurons were measured using intracellular recording techniques in a slice preparation. After each experiment, the recorded neuron was filled with neurobiotin and immunohistochemically identified as 5-hydroxytryptamine (5-HT)-immunopositive or 5-HT-immunonegative. The cellular characteristics of all recorded neurons conformed to previously determined classic properties of serotonergic dorsal raphe nucleus neurons: slow, rhythmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
156
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(178 citation statements)
references
References 42 publications
18
156
0
4
Order By: Relevance
“…Twenty-one neurons were successfully labeled in 20 rats. These neurons were selected (see Materials and Methods) to be representatives of all major raphe cell groups reported in previous studies (10,13,14,18). ʈ Thus, the sample included both theta-on and theta-off units, i.e., cells activated or suppressed during theta and neurons with a wide range of firing rates (0.3-25 spikes per sec) and with a variety of spike waveforms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one neurons were successfully labeled in 20 rats. These neurons were selected (see Materials and Methods) to be representatives of all major raphe cell groups reported in previous studies (10,13,14,18). ʈ Thus, the sample included both theta-on and theta-off units, i.e., cells activated or suppressed during theta and neurons with a wide range of firing rates (0.3-25 spikes per sec) and with a variety of spike waveforms.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the firing of a large population (up to 55%) of raphe neurons in both anesthetized (9)(10)(11) and freely behaving rats (12) appeared phase-locked to hippocampal field potential oscillations at theta frequency. However, raphe neurons with theta-related firing were identified only by indirect electrophysiological criteria, whose reliability was questioned in recent studies by using combined cellular electrophysiology and immunohistochemistry (13)(14)(15). Thus, the important question of how the seemingly homogeneous population of serotonergic neurons is able to participate in the wide range of brain activity remains unanswered.…”
mentioning
confidence: 99%
“…For example, increased 5-HT 1A expression in the ventromedial DRN at the mid-rostral level would be expected to increase somatodendritic autoreceptor tone within this region, reducing serotonin release in terminal fields supplied by those neurons. Alternatively, the 5-HT 1A receptor has been reported on a small number of non-serotonergic neurons in the DRN (Kirby et al, 2003), especially in rostral DRN (Day et al, 2004). If the observed alterations in expression of this receptor reflected changes in this neuronal population, then intra-raphe circuits could also be modulating 5-HT independent of the autoreceptor activity.…”
mentioning
confidence: 99%
“…11,16 However, since the proof of an absence of expression is always subject to debate, we relied on the different methodologies utilized to increase the certitude of the estimate yielded by each technique alone. The occurrence of false negatives cannot be ruled out, and it is possible that in some cells the levels of 5-HT1A transcripts are extremely low and escape detection.…”
mentioning
confidence: 99%
“…This is consistent with immunohistochemical studies that showed a significant percentage of 5-HT cells that do not present immunoreactivity to a 5-HT1A antibody, indicating lack of protein expression. 11,16 In addition, electrophysiological studies where hyperpolarizing responses elicited by superfusion of a 5-HT1A agonist were assessed, found a considerable number of nonresponding identified serotonergic cells. 9,10,12,25 We hypothesized that while following the classic dogma to identify 5-HT neurons, many investigators have discarded data involving 5-HT1A-negative serotonergic neurons.…”
mentioning
confidence: 99%